Exploring mitochondrial DNA variation in the Italian Peninsula - Brisighelli, F; Álvarez-Iglesias, V; Capelli, C; Scarnicci, F; Boschi, I; Luiselli, D; Garagnani, P; Carracedo, A; Salas, A; Pascali, V (2008)
The genetic structure of Italy appears to be mainly shaped by pre-Roman historical events. The studies carried out so far show a major North-South cline, possibly the result of two distinct main demic processes: the first colonisation of the area during the Palaeolithic period and the subsequent Neolithic expansion from the Middle East. However, the demographic contribution of these events is still a matter of debate. We here report mitochondrial DNA (mtDNA) data from nine population groups covering the main Italian regions: Central Liguria (N = 50), East Friuli (N = 51), South Latium (N = 48), Central Marche (N = 53), West Calabria (N = 50), Central Campania (N = 50), South Apulia (N = 53), and two populations from Sicily (East and West Sicily, N = 40 each). Haplogroup frequency spectra indicate clear differences at a regional level and haplotype sharing among populations is low. © 2008 Elsevier Ireland Ltd. All rights reserved.